Patterns of breast cancer mortality trends in Europe - Amaro, J (2013)
Objectives: To identify patterns of variation in breast cancer mortality in Europe (1980–2010), using a model-based approach. Methods: Mortality data were obtained from the World Health Organization database and mixed models were used to describe the time trends in the age-standardized mortality rates (ASMR). Model-based clustering was used to identify clusters of countries with homogeneous variation in ASMR. Results: Three patterns were identified. Patterns 1 and 2 are characterized by stable or slightly increasing trends in ASMR in the first half of the period analysed, and a clear decline is observed thereafter; in pattern 1 the median of the ASMR is higher, and the highest rates were achieved sooner. Pattern 3 is characterised by a rapid increase in mortality until 1999, declining slowly thereafter. Conclusion: This study provides a general model for the description and interpretation of the variation in breast cancer mortality in Europe, based in three main patterns.